Synthesis and characteristics of some new polythiophene containing α, β‐unsaturated carbonyl groups. Issue 5 (21st July 2022) - Duong, Tran Thi Thuy; Dua, Nguyen Thi; Linh, Nguyen Ngoc; Nguyet, Le Thi; Tuyet, Le Thi Minh; Hien, Nguyen; Linh, Duong Khanh; Hung, Ha Manh; Oanh, Doan Thi Yen; Chinh, Nguyen Thuy; Oanh, Vu Thi Ngoc; Ha, Hoang Thu; et al.
Abstract: Some new polythiophenes with α, β‐unsaturated carbonyl groups were synthesized using a chemical oxidative coupling reaction. IR, 1 H‐NMR, UV‐Vis and Raman spectra were used to confirm the expected structure of polymer which is suitable for the suggested synthetic route. Two of all synthesized polythiophenes were soluble well in DMSO and CHCl3 solvent. The morphology, thermal stability, photoluminescence properties and conductivity of polymers were studied. The trans ‐configuration of α, β‐unsaturated carbonyl side chain improve featured properties of these polymers. Abstract : New polythiophenes: High conductivities and promissing photoluminescence materials